Comparison of finger flexor resistance training, with and without blood flow restriction, on perceptional and physiological responses in advanced climbers - Vidar Andersen; Espen Hermans; Vegard Vereide; Nicolay Stien; Gøran Paulsen; Jiří Baláš; Michail Lubomirov Michailov; Helene Pedersen; Atle Hole Saeterbakken (Scientific Reports, 2023)
Abstract This study compared perceptional and physiological responses of finger flexor exercise performed with free flow and blood flow restriction (BFR). Thirteen male advanced climbers completed three sessions of finger flexor resistance exercise at (1) 40% of MVC (Low) and (2) 75% of MVC (High) and (3) BFR at 40% of MVC (Low + BFR) in a randomized and counterbalanced order. Rate of perceived exertion for effort (RPE) and discomfort (RPD), session pleasure/displeasure (sPDF), exercise enjoyment (EES), lactate concentration and oxygen saturation were recorded after the last set. Both low-intensity sessions induced higher RPD than High (p = 0.018–0.022, ES = 1.01–1.09) and High was perceived as more enjoyable than Low-BFR (p = 0.031, ES = 1.08). No differences were found for RPE or sPDF (p = 0.132–0.804). Lactate was elevated more after High than the Low-sessions (p < 0.001, ES = 1.88–2.08). Capillary oxygen saturation was lower after Low + BFR compared to the other sessions (p = 0.031, ES = 1.04–1.27). Finally, the exercise volume was greater in Low compared to High (p = 0.022, ES = 1.14) and Low + BFR (p = 0.020, ES = 0.77). In conclusion, among advanced male climbers, performing Low + BFR led to a similar exercise volume but was perceived as more discomforting and less enjoyable compared to High. The Low session yielded similar responses as the Low + BFR but required a much greater exercise volume.